Preface (Archives of Mechanics - Test, 1999)
The 32nd Solid Mechanics Conference, SolMec'98, followed a long tradition of the Polish Solid Mechanics Conferences organized by the Institute of Fundamental Technological Research of the Polish Academy of Sciences in co-operation with the Committee of Mechanics of the Academy.